A facile electrochemical method for rapid determination of 3-chloropropane-1, 2-diol in soy sauce based on nanoporous gold capped with molecularly imprinted polymer. (April 2022) - Cheng, Weiwei; Zhang, Qiaoyun; Wu, Di; Yang, Yuling; Zhang, Yan; Tang, Xiaozhi
Abstract: 3-monochloropropane-1, 2-diol (3-MCPD) is a well-known heat-produced food contaminant, which has been reported to be carcinogenic, nephrotoxic, and reproductively toxic. In this study, a facile electrochemical sensor based on nanoporous gold (NPG) capped with molecularly imprinted polymer (MIP) was constructed for the rapid and selective determination of 3-monochloropropane-1, 2-diol (3-MCPD). Firstly, NPG was fabricated on the electrode through coating the glass carbon electrode (GCE) surface with NPG film to provide an ideal substrate for polymerization of the MIP membrane and improve the electrocatalysis activity of the sensor. Then, the MIP membrane was constructed on the NPG surface via self-assembly by electropolymerization to realize selective recognition of target 3-MCPD molecules. As a consequence of the combined effect of NPG and MIP, the optimized molecularly imprinted polymer/nanoporous gold/glassy carbon electrode (MIP/NPG/GCE) sensor exhibited outstanding analytical performance towards 3-MCPD with a much wider linear range from 10 −16 to 10 −7 mol/L and fairly low detection limit of 3.5 × 10 −17 mol/L (S/N = 3). Meanwhile, the constructed electrochemical sensor presented outstanding specificity, anti-interference capability, and reproducibility. In order to demonstrate practical applicability, the MIP/NPG/GCE was applied for the detection of 3-MCPD in real soy sauce and satisfactory results were obtained with recovery rates ranging from 105.90% to 107.52%. Highlights: An electrochemical sensor was prepared for detecting 3-MCPD using NPG and MIP. NPG improved the electrocatalysis activity of the sensor. The structure of NPG provided an ideal substrate for polymerization of MIP film. The MIP film self-assembled on NPG realized selective recognition of 3-MCPD. The fabricated sensor showed outstanding analytical performance towards 3-MCPD.